An experimental comparison between commercial hybrid PV-T and simple PV systems intended for BIPV. (October 2018) - Fuentes, M.; Vivar, M.; de la Casa, J.; Aguilera, J.
Abstract: The idea of combining both thermal and photovoltaic collectors in hybrid photovoltaic-thermal (PV-T) modules actually shows a great potential for integration on facades and rooftops of buildings, mainly because of the reduced available space and the benefits of the on-site electricity and thermal generation. The objective of this work is to compare the real performance (experimental data obtained under real sun during a year) of a commercial hybrid PV-T system vs. a simple PV system using microinverters, assessing the suitability of one-unit hybrid PV-T systems vs. two separated units – PV systems + Thermal systems – for building integration. The combined efficiency over the span of a full day could reach values up to 80%, but this apparent high value needs to be analysed in detail. From the experimental results, it can be observed that both systems, PV and PV-T, have a good electrical performance. But the PV-T system output does not benefit from the lower module temperatures that it should achieve from the active cooling in its back, presenting the same performance as the simple PV system. Regarding the microinverters configuration performance, it has been very positive working with high efficiencies above 96%, justifying its use in this type of applications. In conclusion, the commercial PV-T system has not performed as expected, showing problems with the integration of the active cooling in the back of the PV modules. At this moment, and despite the potential of PV-T systems for BIPV due to space limitations, commercial PV-T systems are still far from PV and Thermal systems using separately. Highlights: An experimental study on a commercial PV-T system for buildings was conducted. One-year real performance of PV-T vs. PV system using microinverters was evaluated. Systems exhibited similar electrical performance, PV-T did not benefit from cooling. Cooling circuit in the back of the PV-T module should improve its thermal attachment. Microinverters reached efficiencies of 96%, showing potential for this application.